2008
DOI: 10.1007/s10750-008-9579-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific absorption coefficient and the phytoplankton package effect in Lake Taihu, China

Abstract: In order to investigate variations of absorption and total chlorophyll-a (TChl-a)-specific absorption coefficient of phytoplankton in Lake Taihu, 57 water samples obtained from Lake Taihu during November 8-22, 2007 were used in this study. Package effect and accessory pigments' influences on the absorption spectra were also examined. Phytoplankton absorption was measured by quality filter technical, and TChl-a concentration was measured by ''hot ethanol'' method. Results yielded significant variations in phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 37 publications
7
58
1
Order By: Relevance
“…These authors discovered that the chlorophyll-a specific absorption coefficient a à phy decreases with increasing [Chl-a] at 412, 443 and 490 nm and is lower at 675 nm. This inverse relationship was also reported in previous studies (Le et al 2009a) and may be explained by the fact that an increase in [Chl-a] lead to an increase in the concentration of intracellular pigment or in cell volume rather than in cell number, resulting in an absorption efficiency loss in the package effect. The phytoplankton backscattering efficiency tends to be higher in blue than in red wavelength (Brewin et al 2012), but can be masked due to the package effect.…”
Section: Relationship Between B Bp440 and Tsm Concentrationsupporting
confidence: 83%
“…These authors discovered that the chlorophyll-a specific absorption coefficient a à phy decreases with increasing [Chl-a] at 412, 443 and 490 nm and is lower at 675 nm. This inverse relationship was also reported in previous studies (Le et al 2009a) and may be explained by the fact that an increase in [Chl-a] lead to an increase in the concentration of intracellular pigment or in cell volume rather than in cell number, resulting in an absorption efficiency loss in the package effect. The phytoplankton backscattering efficiency tends to be higher in blue than in red wavelength (Brewin et al 2012), but can be masked due to the package effect.…”
Section: Relationship Between B Bp440 and Tsm Concentrationsupporting
confidence: 83%
“…Lake Taihu is a crucial water source for the Yangtze River Delta, located between 30°56′N-31°33′N and 119°54′E-120°36′E (Figure 1) [30]. In this article, Lake Taihu can be divided into six areas based on shoreline geometry, environmental factors, and human activities: Meiliang Bay, Zhushan Bay, Gonghu Bay, Xukou Bay, East Lake Taihu and the open area ( Figure 1) [32,33].…”
Section: Study Areamentioning
confidence: 99%
“…Besides, Lake Taihu Basin also contributes 11.6% of China's gross domestic product, despite accounting for only 0.38% of China's total area. With economic development, a lot of wastewater, sewage and polluted water surrounding urban and rural areas were discharged to Lake Taihu, resulting in phytoplankton blooms and then triggering a drinking water crisis in 2007 [30]. Phytoplankton are commonly the most important primary producer in lake ecosystems, strongly influencing nutrient concentrations and supporting higher trophic levels such as zooplankton and filter feeders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Prieur & Sathyendranath (1981), Sathyendranath et al (1987), and Gallegos & Correl (1990) found that a Chl * for oceanic and coastal waters varies from 0.01 to 0.047 m 2 mg -1 , whereas Smith & Baker (1981) found that a Chl * varied between 0.039 and 0.168 m 2 mg -1 . On the other hand, Heege , in Albert & Mobley, 2003 and Le et al (2009) Table 3). These results indicate that the Berau estuarine waters have a relative low trophic state.…”
Section: Classification Of Coastal Watersmentioning
confidence: 99%
“…This model has potential of providing accurate retrievals of several parameters because they attempt to model the physics of ocean color (Maritorena et al, 2002). Semi-analytical models have been developed to derive waters constituents such as chlorophyll a (Chl a) concentration, total suspended matter (TSM) concentration, and colored dissolved organic matter (CDOM) absorption (D'Sa et al, 2002;Maritorena et al, 2002;Haltrin & Arnone, 2003;Doerffer & Schiller, 2007;Van der Woerd & Pasterkamp, 2001;Le et al, 2009;Salama & Stein, 2009;Salama & Shen, 2010a).…”
Section: Introductionmentioning
confidence: 99%